Cyber threat hunting - AlFardan, Nadhem (Manning Publications, 2025)
Cyber Threat Hunting teaches you how to conduct structured expeditions using techniques that can detect even the most sophisticated cybersecurity challenges. You'll begin by mastering the fundamentals: formulating a threat hypothesis, gathering intelligence, strategizing your approach, and executing your hunt. From there, you'll explore advanced techniques, including machine learning and statistical analysis for anomaly detection. Using this book's downloadable datasets and scenario templates, you'll get the hands-on experience you need to refine your threat-hunting expertise.
Online resource; title from title details screen (O'Reilly, viewed February 17, 2025)
Keywords: Cyberterrorism -- Prevention; Computer security; Sécurité informatique; Audiobooks; Livres audio